Further psychometric validation of the BODY-Q: ability to detect change following bariatric surgery weight gain and loss. Issue 1 (December 2017) - Klassen, Anne; Cano, Stefan; Kaur, Manraj; Breitkopf, Trisia; Pusic, Andrea
Abstract Background Recent systematic reviews have identified that current patient-reported outcome instruments have content limitations when used to measure change following bariatric surgery. The aim of this study was to measure change after bariatric surgery using the BODY-Q, a PRO instrument designed for weight loss and body contouring. Methods The BODY-Q is composed of 18 independently functioning scales and an obesity-specific symptom checklist that measure appearance, health-related quality of life (HR-QOL) and experience of health-care. The sample for this study included patients who were exploring or seeking bariatric surgery in Hamilton (Canada) at the time of the BODY-Q field-test study and who agreed to further contact from the research team. These patients were invited to complete 12 BODY-Q scales and the symptom checklist between 7 June 2016 and 29 November 2016. Data were collected online (REDCap) and via postal surveys. Clinical change was measured using paired t-tests with effect sizes and standardized response means. Results The survey was completed by 58 of 89 (65%) pre-bariatric participants from the original BODY-Q field-test sample. The non-participants did not differ from participants in terms of age, gender, ethnicity, BMI or initial BODY-Q scale scores. Participants who had undergone bariatric surgery had a mean BMI of 49 (SD = 7) at time 1 and 35 (SD = 7) at time 2. Time since bariatric surgery was on average 2 years (SD = 0.5) (range 0.4 to 3 years). Percentage total weight loss ranged from 12 to 51 (mean 31, SD = 9). The difference in the proportion of patients to report an obesity-specific symptom on the BODY-Q checklist was significantly lower at follow-up for 5 of 10 symptoms. Participants improved on BODY-Q scales measuring appearance (of abdomen, back, body, buttocks, hips/outer thighs, inner thigh), body image and physical function (p  < 0.001 on paired t-tests) and social function (p  = 0.002 on paired t-test). These changes were associated with moderate to large effect sizes (0.60 to 2.29) and standardized response means (0.47 to 1.35). Conclusions The BODY-Q provides a set of independently functioning scales that measure issues important to patients who undergo weight loss. BODY-Q scales were responsive to measuring clinical change associated with weight loss 2 years after bariatric surgery.